How the West Was Won and Where It Got Us: Compressing History in Silius' Punica - Hulls, Jean-Michel (Histos, 2011)
In an intellectual climate where Silius is read with increasing interest, this paper explores the Punica as a historical text. In particular, I examine how Silius includes incidents from outside the time of the Second Punic War within his historio-epic narrative of that period. Careful examination is made of one particular episode, the duel between Italian and Carthaginian brothers at the battle of Ticinus, to see how this reflects upon Rome’s earliest history, especially the duel between the Horatii and Curiatii and Rome’s conquest of Alba. Silius is revealed as an author who can compress history, giving his Punic war narrative a universal relevance, a feature appreciated by his contemporary Martial.